How swimming affects plasma insulin and glucose concentration in Thoroughbreds: A pilot study. (August 2017) - Bonelli, F.; Sgorbini, M.; Meucci, V.; Sighieri, C.; Baragli, P.
Highlights: Training increased insulin-stimulated glucose uptake in skeletal muscle, with a decrease in plasma glucose concentration. Plasma levels of insulin and glucose were evaluated in 12 horses during an IV glucose tolerance test (IVGTT). The IVGTT was performed before and 1 month after training in a swimming pool. Compared to pre-training values, post-training area under the curve increased for plasma glucose, but not for plasma insulin. Low-intensity prolonged swimming exercise might improve glucose metabolism in horses. Abstract: Low intensity exercise increases insulin-stimulated glucose uptake in skeletal muscle and decreases its plasma concentration. In this study, plasma insulin and glucose concentrations were evaluated 5 min before and 5, 15, 25, 35, 45 and 60 min after an IV bolus of glucose in 12 Thoroughbreds before and after 1 month of submaximal aquatraining exercise, monitored using heart rate and blood lactate. Plasma glucose concentrations were evaluated using a colorimetric enzymatic method, and plasma insulin concentrations with a solid-phase radioimmunoassay method. Pre-training plasma glucose concentrations at 15, 25 and 35 min, area under the glucose curve and peak glucose concentration were significantly higher than post-training values ( P < 0.05). Baseline pre-training plasma insulin concentrations were significantly lower than in the post-training period, and plasma insulin was significantly higher at 45 and 60 min in the pre-training period than the post-training period. These results indicate that aquatraining could improve insulin-glucose metabolism in horses.